The Role of Leisure Time Investment in Developing Creativity and Self-actualization Among Young People (A field study on students of the Faculty of Education, Zuwara) (Al-Farooq Journal of Sciences, 2025)
This study aimed to reveal the role of leisure time investment in developing creativity and self-actualization among young people.Using a convenient sample of 42 individuals and employing a questionnaire covering the study's themes, along with the SPSS statistical software, the study arrived at key findings, including: a high level of leisure time investment and a high level of creativity development among the young people in the study sample. This indicates a positive role for leisure time investment in enhancing their creative abilities.The results showed a high level of self-actualization, indicating that investing leisure time contributes positively to enhancing young people's sense of self-actualization and developing their personal aspects. The results also showed a positive correlation between the reality of investing leisure time and the development of creativity among the young people in the study sample, and that the good use of leisure time is an important factor in supporting aspects of personality, and that it is through developing their abilities, enhancing their skills, and helping them to achieve self-actualization in a positive way.